2023
DOI: 10.3390/jcs7010023
|View full text |Cite
|
Sign up to set email alerts
|

On the Influence of Fatigue Damage in Short-Fibre Reinforced Thermoplastic PBT GF30 on Its Residual Strength under High Strain Rates: An Approach towards Simulative Prediction

Abstract: Only by using accurate material data can precise simulation results be achieved. This principle also and especially applies in the field of crash simulation. However, in the simulation of short-fibre reinforced thermoplastics, material parameters are usually used that originate from the material testing of as-new samples. In order to get closer to the condition on the roads, where not only new vehicles are driving, the influence of service loads on the crashworthiness has to be investigated. This paper reports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Further research in the sectors of AM and topology optimization of orthoses was conducted, for example, by Leary et al [24], Lin et al [25], Lin et al [26], and van Lieshout et al [27]. In previous work, material testing and characterization were performed by Witzgall et al [28,29] to provide the basis for usable AM and topology-optimized FRP products. In addition, the study of Valvez et al [30] shows that when fibers were added to plastics, higher stress relaxations and compressive displacements were observed.…”
Section: State Of the Artmentioning
confidence: 99%
“…Further research in the sectors of AM and topology optimization of orthoses was conducted, for example, by Leary et al [24], Lin et al [25], Lin et al [26], and van Lieshout et al [27]. In previous work, material testing and characterization were performed by Witzgall et al [28,29] to provide the basis for usable AM and topology-optimized FRP products. In addition, the study of Valvez et al [30] shows that when fibers were added to plastics, higher stress relaxations and compressive displacements were observed.…”
Section: State Of the Artmentioning
confidence: 99%
“…It has been shown that a temperature increase of more than 10°C can lead to a rapid decrease in strength and undesired thermal failure [14,15]. An excessive temperature rise can be caused by internal friction during testing.…”
Section: Sampling Constraintsmentioning
confidence: 99%
“…NCF-composites can be compromised by defects that arise during manufacture, like voids [3,4] and fibre misalignments [5][6][7]. However, defects can also occur during product use, such as fatigue [8][9][10] or impact [11][12][13]-induced cracks (further on referred to as service-related defects).…”
Section: Introductionmentioning
confidence: 99%
“…Investigations on the influence of voids on the strain-rate-dependent material behaviour of FRP have been presented by the author in [28]. The first approaches for modelling the strain-rate-dependent deformation behaviour have been published for glass-fibrereinforced thermoplastics [10,48,49] and thermosets [8,50,51]. Potentially existing defects due to previous damage caused by service loads are only considered in [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation